Analisis Konten Aktivitas Corporate Social Responsibility Kampanye Goals pada Website MNC Peduli - Nunki Imtinan Valentina; Ratih Hasanah Sudrajat (Universitas Batanghari Jambi, 2023)
This research was conducted to find out the message of the Goal Campaign's Corporate Social Responsibility (CSR) activities in the form of news published by the MNC Group through the MNC Peduli website. In this study, we analyze news message categories, news message content approaches, and CSR news message values. This research was carried out using qualitative methods and content analysis. The findings from this research are that the message categories used by companies in making CSR news messages are hard news and features. The content approach used in creating MNC Peduli's CSR news messages is a social and spiritual approach. MNC Peduli's CSR news message values have fulfilled the five elements of message values. The conclusion of this study is that MNC Group, through MNC Peduli, publishes messages on Corporate Social Responsibility (CSR) campaign goals in the form of published news quite optimally by using categories, content approaches, and values that are in line with stakeholder.